PENURUNAN EMISI GAS BUANG MOTOR DIESEL KAPAL DENGAN ELEKTROLISIS AIR LAUT - I Made Ariana (Purifikasi, 2011)
This research was aimed to simultaneously reduce exhaust emissions from diesel ship engine. Three emission parameters, which consisted of NOx, SOx and particulate matter (PM), were reduced by spraying the electrolysis product of sea water through a scrubber to the exhaust gas. Dong Feng motor diesel, type R175A, with a maximum power of 6.6 HP and rotation rate of 2600 rpm was used in this test. The motor was operated using Marine Diesel Oil fuel up at 2400 rpm in various power loads. Loading was done by an electric generator, which was connected with an electric lamp panel. The loading power was varied at 500, 1500, and 2500 watts. Exhaust gas flow rates into the scrubber were also varied by exhaust pipe valve adjustment. The variations were made 100% and 75% of exhaust gas flow rate to the scrubber. Measurements of pH value and exhaust gas emissions were done near the inlet and the outlet points of the scrubber. Measurements of pH values were carried out near the anode and cathode in order to determine the formation of acid and alkaline solutions to be sprayed into the scrubber. The concentrations of NOx, SOx, and PM were measured at various load variations. Sea water electrolysis produced acid and base, which affected the pH values to change from 5 to 12. This method could reduce NOx, SOx, and PM concentrations up to 76%, 75%, and 42% respectively.